Assessment of the presence of antibiotic residues in meat from small-scale broiler farms in the Pwani region of Tanzania - Rogia Saidath Adeline Gomez; Isabella Mandl; Said Hemed Mbaga (Journal of Agriculture and Rural Development in the Tropics and Subtropics)
The unregulated use of veterinary drugs, particularly antibiotics, on Tanzanian broiler farms is widespread. Still, little attention has been paid to the factors that promote the presence of antibiotic residues in broiler meat. This study aimed to identify rearing practices likely to favour the presence of antibiotic residues and to determine the presence of residues of commonly used antibiotics in broiler meat. The length of the rearing period, poultry pathologies and the type of veterinary medicines used were studied on 78 farms in the Pwani region (Tanzania). The results showed that infectious coryza, coccidiosis, chronic respiratory diseases, salmonellosis and omphalitis were the most common diseases. Of the veterinary medicines used to treat these diseases, antibiotics were the most widely used (69%), mainly enrofloxacin (ENO), limoxin (LX), oxytetracycline (OTC), tylosin (TS) and tylodox (TDX). Eight farms were selected to take broiler meat samples for laboratory analysis of residues of these five antibiotics. These analyses revealed that all but one of the samples were negative. Samples taken from four-week-old birds tested positive for another antibiotic, sulfamethazine (SF), which was not initially one of the five antibiotics selected for this study. This study highlighted the significant use of veterinary drugs in response to various diseases. The absence of antibiotic residues can be attributed to the age of the animals sampled, as at over 5 weeks, they would have had time to eliminate the drugs. A rearing period of four weeks is insufficient and would be a factor favouring the presence of drug residues in broiler meat.